Implementation of Islamic Law in Dealing with Disabled Husbands and Family Support Obligations - Ahmad Syahputra; Maria Fatimah (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2020)
This research examines the implementation of Islamic law in families with husbands who have disabilities, especially related to maintenance obligations. The family is an important social unit in Islam, with the husband as the person responsible for providing support. However, the husband's disability condition creates additional challenges in fulfilling this obligation. Through descriptive and normative approaches, as well as case studies and legal analysis, this research collects data from literature studies, interviews with legal and family experts, and direct observation. The research results show that Islamic law provides flexibility in the division of breadwinner roles, allowing wives to help without reducing their husband's main obligations. Comparative analysis with practices in other Muslim countries shows the importance of government support and social institutions in improving the welfare of families with disabled members. More inclusive policy recommendations and practical solutions based on the principles of Islamic law are proposed to ensure the overall well-being of families.